IMAGE CONTENT SOFTWARE ANALYSIS - HAMBALÍK, Alexander; MARÁK, Pavol (Trends in education, 2015)
This contribution provides an overview of present methods for processing and verifying authenticity of digital images. It also discusses a topic of fingerprint image processing. Their appropriate application allows to reveal modified image parts before being released to public. Moreover, they help us perform an automated comprehensive analysis of fingerprint image properties that is still a challenging task in the field of forensic science.
Keywords: image content analysis; authentication; fingerprint image properties.